STATISTICAL ANALYSIS OF EMPLOYMENT OF GRADUATES OF EDUCATIONAL ORGANIZATIONS - A. Anferov; E. Dolgikh (Вестник университета)
The basic results of sampling of graduates of educational organizations in 2010-2015 are considered. The analysis of dynamics of the number of graduates during their employment was carried out. The results of employment of graduates in the rst job are evaluated. The situation of graduates in the labor market in 2016 as well as their wages and the distribution of the spheres of labor activity are analyzed. Special attention is paid to assessing the satisfaction of graduates with work. The characteristic of unemployment among graduates of educational organizations of 2010-2015 is given.